Study of V2V Communications on Mumbai-Pune Express Highway - Khairnar, Vaishali D.; Pradhan, S. N. (Asian Journal of Engineering and Applied Technology, 2012)
This paper presents a detailed study of short range communications between vehicles in a realistic Mumbai-Pune Express (MPE) highway scenario. This paper will show the expected wireless communication characteristics in a vehicle driving environment and identify the factors that significantly affect V2V communication performance. It is also illustrated to broadcast different emergency messages according to the different factors identified (e.g. whether, road condition, vehicle traffic emergency message to avoid collision etc.).